In vitro aggregation of the gene-sized DNA molecules of the ciliate Stylonychia mytilus. - Lipps, H J (1980)
Macronuclear DNA of hypotrichous ciliates exists in the form of gene-sized DNA molecules. It can be resolved on agarose gels into a continuum of sizes upon which is imposed a set of characteristic DNA bands. Most or all of the DNA molecules carry identical terminal inverted repeat sequences. By incubating macronuclear DNA under increasingly stronger ionic conditions, high molecular weight DNA aggregates and ring-like DNA structures are formed. Experimental evidence is presented that this aggregation is not due to the presence of identical single-stranded DNA ends on each macronuclear DNA fragment, and an alternative model for DNA aggregation is discussed.